STAKEHOLDER PREFERENCES FOR FISHERIES MANAGEMENT IN PREVENTING MARINE POLLUTION (CASE STUDY OF KMN. BUKIT SAFA BASED AT THE OCEANIC FISHING PORT KENDARI, INDONESIA) - Sari, Iya Purnama; Sarasati, Wulandari; Hidayat, Inzaghi Akbar (Jurnal Penelitian Perikanan Indonesia, 2025)
Coastal areas support human activities, namely to ensure the sustainability of their lives through fishing activities. Fishing activities produce residual components in the form of marine debris and oil or fuel spills. Marine debris and oil or fuel spills are the main sources of marine pollution, so stakeholder preferences for solutions provided to overcome these problems need to be studied in order to support the sustainability of fisheries management. The research was conducted in February-March 2024. The purposive sampling method was used by selecting fishing vessels with purse seine gear with one vessel, namely KMN. Bukit Safa based in Samudera Fishing Port, Kendari. In addition, interviews were conducted with 15 respondents who are fisheries stakeholders at PPS Kendari. Data analysis used the Pollution Prevention Approach (PPA) model. The results of the identification of residual components from fishing activities on KMN. Bukit Safa included marine debris and oil and fuel spills. Preventive methods are important in this case to prevent marine pollution so that fish habitat conditions can be maintained so that they can support fisheries management. Stakeholder preferences related to recommended solutions in dealing with residual components to prevent marine pollution so as to support fisheries management, namely recommendations to bring back garbage to sea as a condition for issuing a sailing approval letter and rechecking the ship so that there are no obstacles are high with a weight of over 60% each.